Pengaruh Kepemimpinan Transformasional, Dukungan Organisasional Yang Dipersepsikan dan Motivasi Kerja Terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Bombana: Indonesia - Muhammad Fathir Maulid Yusuf, Abdul Suharno Wahid, Ilham Akbar Garusu, Dian Mayafaty Rauf, Ahmad Ham (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
This study examines the influence of transformational leadership, perceived organisational support, and work motivation on employee performance, with a focus on low employee performance that affects the effectiveness and efficiency of public services. The research method used a quantitative method, where data was collected through questionnaires and analysed using multiple linear regression. The results showed that transformational leadership, perceived organisational support, and work motivation have a significant influence on employee performance. Leaders who are able to inspire and motivate subordinates, as well as organisational support perceived by employees, tend to improve their performance. The findings emphasise the importance of effective leadership, organisational support, and work motivation to improve employee performance. The results of this study are expected to serve as a reference for policy making and human resource development strategies in local government.